Efeitos da obesidade na morfologia muscular e na junção neuromuscular dos músculos tibial anterior, vasto lateral e medial de ratos - Piazzi, Isabela (Universidade Federal de São Carlos, 2020)
Obesity affects several body tissues, however it is not yet clear whether the neuromuscular system can also change. The objective of this study was to analyze morphological aspects of the neuromuscular junctions (NMJ) and adaptations of the vastus lateralis (VL), vastus medialis (VM) and anterior tibialis (TA) muscles and serum cytokine concentration in Wistar rats, after a period of 28 weeks fed an obesity-inducing diet. Two groups of male rats aged 6 weeks were analyzed: DIO (obesity-inducing diet, n = 5) and control (standard diet, n = 5). After euthanasia, circulating levels of IL-6, TNF-α, leptin and adiponectin were analyzed in the serum. The VL, VM and TA muscles were removed for analysis of morphometric parameters. Measurements were made of the cross-sectional area (CSA) of the muscle fiber, fat quantification and intramuscular connective tissue. Measurements of the total area, perimeter and maximum diameter of the NMBs of the aforementioned muscles were also performed. All data were assessed for normality using the Shapiro-Wilk test and later a comparison was made between groups. In cases where the parametric assumptions were reached (p≥0.05), Student's t test was used and when not, the Mann Whitnney test. Spearman's correlation coefficient was used to analyze the relationship between pro-inflammatory cytokines (IL-6 and TNF-α) and the sarcopenia index. The DIO group demonstrated increases in leptin levels (p = 0.033) and decreases in adiponectin levels (p = 0.002). The VM muscle showed an increase in the area, perimeter and maximum diameter of the NMN, as well as an increase in intramuscular fat (p = 0.001) and connective tissue (p = 0.005). A reduction in the CSA of the muscle fiber of the VM was also observed in the DIO group (p = 0.021). We can conclude that obesity, in the tested model, promoted a remodeling of the NMBs of the studied muscles, accompanied by muscle atrophy, as well as increased intramuscular fat and circulating adipokines, showing that obesity can affect the function of muscle tissue.
Effects of obesity on muscle morphology and neuromuscular junction of the anterior tibial, vastus lateralis and medial muscles of rats
Keywords: Sistema nervoso periférico; Tecido adiposo; Atrofia; Músculo esquelético; Citocinas; Inflamação sistêmica; Eripheral nervous system; Adipose tissue; Atrophy; Skeletal muscle; Cytokines; Systemic inflammation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL